Using Motivational Interviewing to Address Tobacco Cessation: Two Standardized Patient Cases for Pediatric Residents - Rachel Boykan; Robyn Blair; Perrilynn Baldelli; Susan Owens (Association of American Medical Colleges, 2019)
Introduction Motivational interviewing (MI) is a well-established evidence-based method of working with patients to promote health behavior change. Standardized patient (SP) simulation allows trainees to practice and receive feedback on clinical and communication skills and may be useful in applying MI techniques to address tobacco use and exposure. Methods We developed two SP cases for pediatric residents to practice addressing tobacco use with parents of their patients. Results Thirty-six residents participated, 26 of whom had prior MI training. Resident postencounter self-reflection identified MI-specific skills, including eliciting the SP's view on positive/negative aspects of smoking, identifying stressors/triggers associated with smoking, eliciting reasons for smoking, asking about motivation/willingness to quit, eliciting benefits of quitting smoking, letting the SP do the talking, and guiding the SP in making a quit plan. On paired-samples t tests, resident self-evaluation checklist scores averaged 6.79 out of 8.00 (SD = 1.018, SEM = 0.165), compared with SP checklist scores, which averaged 7.08 out of 8.00 (SD = 1.217, SEM = 0.197). Discussion These two SP cases were useful in many ways, allowing residents with prior MI training the opportunity for practice/feedback on skills learned and introducing residents with no prior MI training to MI concepts through experience/feedback. Residents consistently identified using MI concepts on postencounter self-reflection; resident self-evaluation and SP evaluation of residents showed agreement. These sessions could be utilized within a communication/MI curriculum or as stand-alone sessions to introduce MI concepts/techniques for addressing tobacco cessation in the pediatric setting.